Applications of Hankel and Regular Matrices in Fourier Series - Abdullah Alotaibi; M. Mursaleen (Abstract and Applied Analysis)
Recently, Alghamdi and Mursaleen (2013) used the Hankel matrix to determine the necessary and suffcient condition to find the sum of the Walsh-Fourier series. In this paper, we propose to use the Hankel matrix as well as any general nonnegative regular matrix to obtain the necessary and sufficient conditions to sum the derived Fourier series and conjugate Fourier series.